Calling a Notary by Police Investigator Regarding the Relaas Deed Made by a Notary (Case Study at Unit I Pidum Sat Reskrim West Lombok Regional Police) - Sarwoto, Lalu Henry; Parman, Lalu; Munandar, Aris (International Journal of Scientific Research and Management (IJSRM), 2019)
In Article 66 of Law No. 2 of 2014 in conjunction with Law No. 30 of 2004 concerning Notary Position (UUJN), namely: a. If needed by law enforcers in the judicial process, namely the investigator, public prosecutor or judge can submit a request for approval in order to summon a notary. The letter was submitted to the Honorary Board of Notaries; b. Within a maximum of 30 working days from the receipt of the letter of request, the Honorary Board of Notaries must provide the answer; c. If within the period of time determined by the Honorary Board of Notaries does not provide the answer, then the notary Honorary Council's silence is deemed to have received the request for approval. So that law enforcement can make calls to the notary concerned; d. After obtaining approval from the Notary Honorary Assembly, law enforcers are authorized to: 1. Request and take a photocopy of the Minuta deed and / or letters that have been attached to the Minuta deed in the notary deposit (notary protocol); 2. Calling a notary to attend the criminal examination process relating to the notary deed or protocol that is in storage. This type of thesis is normative juridical research that is descriptive analytical, meaning that a data analysis based on general legal theory is applied to explain another set of legal materials. Conclusion: 1. Investigators are authorized to examine Notaries, where Investigators are authorized to receive reports or complaints about criminal acts, seek information and evidence, order to stop suspected persons or ask and examine personal identification and conduct other actions according to law, they can also acting on the orders of investigators to make arrests, forbid leaving search sites and confiscating them. 2. The procedure of investigation is carried out on a Notary after reporting on the Deed made by a Notary, and in the report stated that the Notary has committed a Criminal Act as stipulated in Article 66 of the UUJN. However, the summons of a Notary as a witness, suspect or defendant after the investigator submits a written request to the Regional Supervisory Board and the request is sent to the Notary by making an excuse rather than calling the Notary as a witness, suspect or defendant. After the issuance of the new Notary Position Act, based on Article 66 paragraph I of Act Number 2 of 2014 concerning the current Notary Position, the summons made by the investigator is considered valid if the investigator mentions the reason for the summons clearly, and the caller is Acts that are accountable according to the law are not in conflict with the law, in line with legal obligations, reasonable, reasonable within the investigator's office, based on proper consideration and respect for human rights.